2008
DOI: 10.2967/jnumed.108.050740
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Efficacy of a Small CdTe γ-Camera for Sentinel Lymph Node Biopsy

Abstract: We previously reported the basic performance of a prototype small cadmium telluride (CdTe) g-camera (SSGC) intended for use in radioguided surgeries. In this study, we sought to confirm the favorable previous results and to extend the preliminary findings to examine the efficacy of the SSGC in an animal study and a clinical setting for sentinel lymph node biopsy. Methods: The prototype SSGC (1,024 pixels; field of view, 44.8 · 44.8 mm), equipped with a parallel-hole collimator, was used in both animal and clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…The authors of that study concluded that intraoperative real-time images provide high detection rates in cases of difficult sentinel node localization (11). Reports of intraoperative imaging of sentinel nodes in breast cancer and head and neck tumors have also shown favorable results (8)(9)(10)(11)(12)(13). In prostate cancer, many direct draining nodes have been reported to be localized outside the obturator fossa (2,12) and even outside the area of extended pelvic lymphadenectomy (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of that study concluded that intraoperative real-time images provide high detection rates in cases of difficult sentinel node localization (11). Reports of intraoperative imaging of sentinel nodes in breast cancer and head and neck tumors have also shown favorable results (8)(9)(10)(11)(12)(13). In prostate cancer, many direct draining nodes have been reported to be localized outside the obturator fossa (2,12) and even outside the area of extended pelvic lymphadenectomy (4).…”
Section: Discussionmentioning
confidence: 99%
“…Portable g-cameras have been developed to provide intraoperative radioguidance, and a recent application has been intraoperative identification of radioactive lymph nodes (7)(8)(9)(10). In urologic malignancies, sentinel nodes could be visualized in 90% of the patients and the use of a pointer enabled exact localization of the hot nodes (6).…”
mentioning
confidence: 99%
“…In skin malignancies, the SN uptake is usually minimal, less than 1% of the radiotracer activity [15,16], making SN activity below 100 kBq quite common in surgical practice. In addition, a widely accepted criterion of effectiveness for melanoma SN biopsy is based on an activity threshold: the empirical rule is that any lymph node (LN) with a count rate 10% or greater than that of the highest count rate SN should be excised to reduce the risk of overlooking LN metastases [17].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, many laboratories and companies have developed hand-held g-cameras with different technologies (8)(9)(10)(11)(12)(13)(14)(15). Some of them have been evaluated in different clinical applications such as parathyroid imaging (16)(17)(18)(19), brain (20), bone tumors (21,22), and SNB procedures in BC (21,(23)(24)(25)(26)(27)(28)(29)(30) and more recently in melanoma and gynecologic cancers (31), head and neck cancers (32), and prostate (33) or other urologic cancers (34).…”
mentioning
confidence: 99%